Swallows : a novel - Kirino, Natsuo, 1951- (Alfred A. Knopf, 2025)
"When a young single woman in Tokyo decides she's ready to sell anything-even her womb-to escape the precarity of her life, an agency pairs her with a wealthy couple desperate to have a child. The match seems made in heaven. She even looks a little like the wife. But is anything ever that simple? Nothing has ever gone right for Riki. She left her boring hometown in Hokkaido, where she worked at a nursing home, for a better life in Tokyo. But as a temp in the big city she has no job security, and barely scrapes by. She eats the same old discount boiled egg for lunch every day, sometimes for dinner, too. Many of her peers have to take on a side hustle just to make ends meet. So when her friend discovers an agency offering a hefty sum for egg donation, both leap at the chance for an interview. Meanwhile, former ballet star Motoi Kusaoke and his wife, Yuko, have been trying to conceive for years. After trying what feels like every available option, it seems futile-until Motoi dives deep into his research and learns that, while surrogacy is technically illegal in Japan, there is a company that's found a loophole. Before long, everyone has an opinion on the matter: from Yuko's sex-obsessed, asexual best friend, to Motoi's controlling prima ballerina mother, and even the affable sex-worker-slash-therapist that Riki has been to a couple of times, after she accepted a down-payment to be a surrogate. Acutely funny and addictively page-turning, Swallows pulls at the seams of society, reassessing our understanding of motherhood, self-worth, bodily autonomy, and class. What does it mean to be "in control"? And can money really buy happiness?"--